Biomass-based carbon quantum dots and their agricultural applications - Zihao Dong; Jie Qi; Lin Yue; Han Zhou; Lu Chen; Jiangjiang Gu; Ying He; Honghong Wu (Plant Stress, 2024)
Carbon quantum dots (CQDs), which belong to the category of zero-dimensional nanomaterials, exhibit remarkable properties including chemical stability, water dispersion, low cytotoxicity, small size, biocompatibility, and photoluminescence. Although there are several methods for production of CQDs, there is an increasing interest in using low-cost and environmentally friendly synthetic methods. Biomass-based CQDs are a branch of CQDs which are considered the most ideal fluorescent nanomaterial by green synthesis strategy. The typical green route can be the conversion of waste products into high-value biomass-based CQDs, reducing resource waste and enabling sustainable development. This review will emphasize the benefits of biomass-based CQDs in synthetic methods, material properties, and their research in the area of biology. Additionally, the applications of biomass-based CQDs as plant growth promoters and sensors, and for improving plant stress tolerance and bioimaging were also discussed. Herein, this review summarizes the current investigations on synthesis of biomass-based CQDs from 1970 to 2023 and their application in agriculture. The objective of the review article is to use different biomass-based CQDs to improve plant resistance in stressful environments, so as to make plant growth better. In a word, biomass-based CQDs have strong potential in sustainable agricultural development.